Evaluation of microbiological, physico-chemical, and sensory of canned tilapia fish in different types of sauces (Research, Society and Development, 2022)
Nile tilapia is identified as a freshwater species that can be used as an alternative for canned fish production, as it is widely cultivated in the country and popular among consumers. The objective was to evaluate canned tilapia fillet (Oreochromis niloticus) in different cover sauces: water and salt; edible oil and sauce with tomato, the company is conducting microbiological, physicochemical, and sensory analyses at 15 months of storage to test the hypothesis of the quality and acceptance of the product after the storage time. The tilapia were obtained from a fish warehouse located in the microregion of Toledo, Paraná, Brazil, and industrially canned in a plant with the Federal Inspection seal, following the current commercial and sanitary procedures. The products met the standard required by sanitary regulations. The microbiological and centesimal analyses were performed in the laboratory, following international standards. The experimental sensory analysis was performed according to Dutcosky's methodology and an entirely randomized design was applied for the analysis of variance of the attributes. The tilapia with tomato sauce and edible oil sauce obtained statistically equal means, being preferred by the judges. Therefore, the canning of fillets in tomato and edible oil sauces proved to be an alternative to contribute to the shelf life and the possibility of adding value to the raw material. Result attributed to the practicality of the seasoned product. Canning with natural sauce showed slightly lower results, yet the results indicate a good degree of potential.